Anticipando correcciones desde el aula virtual extendida - Galván, Luis Ariel (2018)
The objective of this work was to be able to make the returns, of the Practical Works (PWs) made by the students, before the presentation of their works printed on paper. From this change, and from the first delivery of their finished digital works, and with the use of the Extended Virtual Classroom, it was possible to provide the student with the status of each of their works and allow corrections of them, before the presentation printed on paper.